Sejarah Perbedaan Pendapat Para Ulama’ Madzhab Dan Implikasinya Kepada Ummat - Dewi Nafisatul Curo’; Elsa Dwi Rahmawati; Rizky Aziz Romadhoni (CV. ITTC INDONESIA, 2024)
Madzhab in Islam refers to a school of legal thought that is based on the interpretation of the main sources of Islam, namely the Koran and Hadith. After the Prophet died, no more revelations came down. Therefore, the ulama then understand and apply Islamic law based on the existing Qur'an and hadith. In an effort to understand laws that are unclear or do not yet have clear texts, the ulama' began to develop ijtihad methods, including ijma' and qiyas. This knowledge was brought in to make it easier to answer problems that arose. in making ijma' and making qiyas not everyone can and is able to do it, high credibility is needed in studying and understanding the Al-Qur'an and Hadith. Differences in madhhab arise due to differences in understanding of manuscripts (texts), hadith, language rules, and also differences in ijtihad method. Geographical, social and political factors also influence the development of madhhab. This abstract will briefly discuss the history of the development of madhhabs and the implications of the differences in madhhabs in the context of Muslim life.